Health Branding, Digital Transformation, and the Content Commodification: A Brand Discourse Analysis of Halodoc - Hendra Agustian; Mochamad Kresna Noer (Jobmark: Journal of Branding and Marketing Communication, 2023)
Amidst the digital communication revolution, health platforms like Halodoc are strategically harnessing the power of social media to engage with their audiences. This study dissects the meticulous construction of Halodoc's brand discourse and the commodification of content on the Instagram platform. Employing the Brand Discourse Analysis (BDA) method and a critical political economy framework, this qualitative research scrutinizes 457 posts from Halodoc's Instagram account from January to June 2023. The findings underscore Halodoc's systematic optimization of the brand message, mode, medium, and milieu as components of brand discourse to craft a brand image as a modern, caring, and trustworthy health partner, effectively driving high user engagement. Furthermore, the commodification analysis uncovers that Halodoc implements a dual commodification model: free health information is transformed into a commodity to captivate audience attention (the first commodification), which is then converted into customers for paid services on its application (the second commodification). This strategy, woven into a narrative of empowerment, effectively turns health discourse into an economic asset within the digital capitalism ecosystem.